Konkurencyjność zamówień publicznych - analiza na podstawie sprawozdań podmiotów zamawiających z lat 2004-2005 - Starzyńska, Wacława; Popławski, Sławomir (Competitiveness - Analysis Based on the Annual Reports of Purchasing Entities from the Years 2004-2005, 2007)
One key consideration in quantifying procurement markets relates to selection of the data sources. The logical choice falls on purchasing entities which have been obliged to make their annual reports permitting identification of quantity and value of public procurements since 2004. The paper tries to analyze changes in structure of awards contracts in the years 2004-2005 based on data coming from annual reports which are collected by the Public Procurement Office in Warsaw. In particularly, the authors stress that Poland adopted a series of the European Union directives regulating in detail award procedures which extent improvements in the competitiveness and transparency of the public procurement markets focusing on works, supplies and services.One key consideration in quantifying procurement markets relates to selection of the data sources. The logical choice falls on purchasing entities which have been obliged to make their annual reports permitting identification of quantity and value of public procurements since 2004. The paper tries to analyze changes in structure of awards contracts in the years 2004-2005 based on data coming from annual reports which are collected by the Public Procurement Office in Warsaw. In particularly, the authors stress that Poland adopted a series of the European Union directives regulating in detail award procedures which extent improvements in the competitiveness and transparency of the public procurement markets focusing on works, supplies and services.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1159, s. 408-419